Ventricular Assist Device Driveline Infections: A Systematic Review - Krzelj, Kristina; Petricevic, Mate; Gasparovic, Hrvoje; Biocina, Bojan; McGiffin, David (The Thoracic and Cardiovascular Surgeon, 2021)
Infection is the most common complication in patients undergoing ventricular assist device (VAD) implantation. Driveline exit site (DLES) infection is the most frequent VAD infection and is a significant cause of adverse events in VAD patients, contributing to morbidity, even mortality, and repetitive hospital readmissions. There are many risk factors for driveline infection (DLI) including younger age, smaller constitution of patients, obesity, exposed velour at the DLES, longer duration of device support, lower cardiac index, higher heart failure score, DLES trauma, and comorbidities such as diabetes mellitus, chronic kidney disease, and depression. The incidence of DLI depends also on the device type. Numerous measures to prevent DLI currently exist. Some of them are proven, whereas the others remain controversial. Current recommendations on DLES care and DLI management are predominantly based on expert consensus and clinical experience of the certain centers. However, careful and uniform DLES care including obligatory driveline immobilization, previously prepared sterile dressing change kits, and continuous patient education are probably crucial for prevention of DLI. Diagnosis and treatment of DLI are often challenging because of certain immunological alterations in VAD patients and microbial biofilm formation on the driveline surface areas. Although there are many conservative and surgical methods described in the DLI treatment, the only possible permanent solution for DLI resolution in VAD patients is heart transplantation. This systematic review brings a comprehensive synthesis of recent data on the prevention, diagnostic workup, and conservative and surgical management of DLI in VAD patients.
Keywords: cardiac; circulatory assist devices; infection; heart failure; wound healing; wound infection